Human bocavirus amongst an all‐ages population hospitalised with acute lower respiratory infections in Cambodia. Issue 2 (25th April 2012) - Arnott, Alicia; Vong, Sirenda; Rith, Sareth; Naughtin, Monica; Ly, Sowath; Guillard, Bertrand; Deubel, Vincent; Buchy, Philippe
<x xml:space="preserve">Abstract</x> Please cite this paper as: Arnott et al. (2013) Human bocavirus amongst an all‐ages population hospitalised with acute lower respiratory infections in Cambodia. Influenza and Other Respiratory Viruses 7(2) 201–210. Background Human bocavirus (HBoV) is a novel parvovirus that is associated with respiratory and gastrointestinal tract disease. Objectives To investigate the prevalence and genetic diversity of HBoV amongst hospitalized patients with acute lower respiratory infection (ALRI) in Cambodia. Study Design Samples were collected from 2773 patients of all ages hospitalised with symptoms of ALRI between 2007 and 2009. All samples were screened by multiplex RT‐PCR/PCR for 18 respiratory viruses. All samples positive for HBoV were sequenced and included in this study. Results Of the samples tested, 43 (1·5%) were positive for HBoV. The incidence of HBoV did not vary between the consecutive seasons investigated, and HBoV infections were detected year‐round. The incidence of HBoV infection was highest in patients aged <2 years, with pneumonia or bronchopneumonia the most common clinical diagnosis, regardless of age. A total of 19 patients (44%) were co‐infected with HBoV and an additional respiratory pathogen. All isolates were classified as HBoV type 1 (HBoV‐1). High conservation between Cambodian NP1 and V1V2 gene sequences was observed. Conclusions Human bocavirus infection can result in serious illness, however is frequently detected in the context of viral co‐infection. Specific studies are required to further understand the true pathogenesis of HBoV in the context of severe respiratory illness.